Influência de diferentes graus de deficiência intelectual nas doenças cárie e periodontal - Costa, Antônio Augusto Iponema (2014)
The oral health care are of fundamental importance for the preservation the integrity of the individual and, consequently, affect general health. The proposition of this observational, cross-sectional analytical study was to assess the oral status of 147 students with intellectual disabilities enrolled in the Association of Parents and Friends of Exceptional Children (APAE) Passo Fundo / RS , Marau / RS and Casca / RS and compare them by level of intellectual disability as to the experience of dental caries and periodontal disease. For this were used the DMFT index, dmft, PSR and a questionnaire, being conducted by a single examiner. The data were subjected to Analysis of Variance (ANOVA) and Tukey test, on a significance level of 5%. There were statistical differences in the DMFT index, with the average of 2.27, 3.76 and 0.58 for students with mild, moderate and severe intellectual disabilities, respectively. Regarding the dmft index results were 1.48, 1.55 and 2.75, and for PSR examination, the majority of respondents (43%), gingivitis showed no retention factor. Students with severe intellectual disabilities possessed better conditions (DMFT) oral health however, for examinations dmft and PSR had no statistical differences between the groups surveyed. It was concluded that students with severe disabilities had better oral health conditions for the DMFT index due care be undertaken by responsible and socioeconomic conditions of the mother (income and education level) influenced the oral health of people with disabilities